Typologie stanów rzeczy - Prokopczuk, Aleksiej (Przegląd Rusycystyczny, 2009)
TYPOLOGIES OF STATES OF AFFAIRS Summary A number of typologies of states of affairs/situations/propositions have been proposed in the literature. Those typologies differ in many ways. In a bottom-up approach, the types of verbs/predicates as individual base elements are fi rst specifi ed in great detail. Behind each class of situations stands a class of verbs. In a top-down approach, an over-view of the system, of the type of discourse or text as phenomena of human communica-tion and interaction is fi rst undertaken. The analysis constitutes an attempt to show the inadequacy of the accounts using an approach to the whole as a sum of its parts. TYPOLOGIE STANÓW RZECZY Streszczenie W literaturze przedstawiono wiele typologii stanów rzeczy, spraw czy sytuacji, które pod wieloma względami różnią się między sobą. W artykule tym szczegółowo określone są wpierw, zgodnie z podejściem indukcyjnym, typy czasowników/predykatów jako elementy podstawowe. Za każdą kategorią sytuacji stoi odpowiednia klasa czasowników. Z kolei podejście dedukcyjne pozwala na podjęcie próby omówienia systemu, typu dyskursu czy tekstu w ramach zjawiska ludzkiej komunikacji i interakcji. Analiza ma na celu wykazanie nieadekwatności typologii przy zastosowaniu podejścia do całości jako sumy jej części.